Genome-wide association study reveals genomic loci of sex differentiation and gonadal development in Plectropomus leopardus - Gao, Jin; Wang, Yongbo; Liu, Jinye; Chen, Fuxiao; Guo, Yilan; Ke, Hongji; Wang, Xulei; Luo, Ming; Fu, Shuyuan (Frontiers in Genetics, 2023)
Plectropomus leopardus, a commercially significant marine fish, is primarily found in the Western Pacific regions and along the coast of Southeast Asia. A thorough analysis of the molecular mechanisms involved in sex differentiation is crucial for gaining a comprehensive understanding of gonadal development and improving sex control breeding. However, the relevant fundamental researches of P. leopardus are relatively lacking. In this study, a genome-wide association study (GWAS) was conducted to investigate the genetic basis mechanism of sex differentiation and gonadal developmental traits in P. leopardus utilizing about 6,850,000 high-quality single-nucleotide polymorphisms (SNPs) derived from 168 individuals (including 126 females and 42 males) by GEMMA (Genome-wide Efficient Mixed Model Association algorithm). The results of these singletrait GWASs showed that 46 SNP loci (-log10P >7) significantly associated with sex differentiation and gonadal development traits were distributed in multiple different chromosomes, which suggested the analyzed traits were all multi-locus control of complex traits. Furthermore, a total of 1,838 potential candidate genes were obtained by considering a less-stringent threshold (-log10P >6) and ±100 kb regions surrounding the significant genomic loci. Moreover, 31 candidate genes were identified This is a provisional file, not the final typeset article through comprehensive analysis of significant GWAS peaks, Gene Ontology (GO) annotations, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses, including taf7, ddx6, apoeb, sgk1, a2m, usf1, hsd3b7, dll4, xbp1, tet3, esr1, gli3 and so on. These trait-associated genes have been shown to be involved in germ-line development, male sex differentiation, gonad morphogenesis, hormone receptor binding, oocyte development, male gonad development, steroidogenesis and estrogensynthetic pathway, etc. In the present study, multiple genomic loci of P. leopardus associated with sex differentiation and gonadal development traits were identified for the first time by using GWAS, which provided a valuable resource for further research on the molecular genetic mechanism and sex control in P. leopardus. Our results also can contribute to the understanding the genetic basis of sex differentiation mechanism and gonadal development process in grouper fishes.